A two-component carbon-based waterproof coating and its preparation method

By designing a two-component carbon-based waterproof coating, the synergistic effect of chitosan-modified polyurethane and photocatalysts was utilized to solve the problem of insufficient formaldehyde adsorption capacity of polyurethane waterproof coatings, achieving efficient formaldehyde removal and improved mechanical properties.

CN120329853BActive Publication Date: 2025-11-14JIANGXI STAR HIGH-TECH MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510695869.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-11-14
Estimated Expiration
2045-05-28

AI Technical Summary

Technical Problem

Existing polyurethane waterproof coatings have insufficient formaldehyde adsorption capacity and poor compatibility with the substrate, resulting in a decline in the mechanical properties of the coating and increasing the safety risks to the home environment.

Method used

The coating is a two-component carbon-based waterproof coating. Component A contains chitosan-modified polyurethane and composite fillers, while component B contains hydrogen-containing silicone oil. Through the synergistic effect of chemical adsorption and photocatalysis, the formaldehyde removal efficiency is improved and the compatibility is enhanced.

Benefits of technology

It achieves efficient formaldehyde removal, improves the mechanical properties and compatibility of the coating, reduces secondary pollution, and provides excellent waterproof performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of coating technology and discloses a two-component carbon-based waterproof coating and its preparation method. The coating includes component A: by mass parts: 80-120 parts chitosan-modified polyurethane, 4-8 parts chitosan, 10-12 parts filler, 0-0.1 parts wetting agent, and 0-0.1 parts defoamer; component B: by mass parts: 10-15 parts hydrogen-containing silicone oil and 0.01-0.02 parts catalyst; the preparation steps of chitosan-modified polyurethane are as follows: polytetrahydrofuran ether diol and isophorone diisocyanate are added to ethyl acetate and stirred evenly, dibutyltin dilaurate is added dropwise, and the reaction is carried out at 75-77°C for 2-4 hours, chitosan composition is added, dibutyltin dilaurate is added again, and the reaction is continued at 75-77°C for 4-8 hours, fluorophenol is added, and the reaction is kept at this temperature for 0.5-2 hours. The solvent is removed to obtain chitosan-modified polyurethane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating technology and discloses a two-component carbon-based waterproof coating and its preparation method. Background Technology

[0002] Polyurethane waterproof coatings exhibit good film elongation, adhesion, and adaptability to substrate cracks and deformation, enabling them to accommodate substrate deformation and prevent damage to the waterproof layer caused by substrate cracking. They are widely used in the field of building waterproofing. Formaldehyde is unavoidable in building materials such as plywood, various engineered wood products, paints, and additives, significantly increasing the safety risks to the home environment. Formaldehyde is highly irritating to humans, and long-term exposure can adversely affect lung, liver, and immune functions, and may even cause cancer. However, existing polyurethane waterproof coatings with formaldehyde adsorption capabilities suffer from insufficient adsorption capacity and poor compatibility between adsorption aids and the substrate, leading to a decline in the coating's mechanical properties. Therefore, researching a waterproof coating with good mechanical properties and strong formaldehyde adsorption capacity, along with its preparation method, is of great significance. Summary of the Invention

[0003] The purpose of this invention is to provide a two-component carbon-based waterproof coating and its preparation method, so as to solve the problems mentioned in the background art.

[0004] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a two-component carbon-based waterproof coating, comprising component A and component B; component A comprises the following raw materials, by mass parts: 80-120 parts chitosan-modified polyurethane, 4-8 parts chitosan (powder), 10-12 parts filler, 0-0.1 parts wetting agent, and 0-0.1 parts defoamer; component B comprises the following raw materials, by mass parts: 10-15 parts hydrogen-containing silicone oil and 0.01-0.02 parts catalyst.

[0005] In a more optimized manner, the preparation of the chitosan-modified polyurethane includes the following steps: adding polytetrahydrofuran ether diol-2000 and isophorone diisocyanate to ethyl acetate and stirring until homogeneous; adding dibutyltin dilaurate dropwise and reacting at 75-77°C for 2-4 hours; adding the chitosan composition and supplementing with dibutyltin dilaurate; continuing the reaction at 75-77°C for 4-8 hours; adding fluorophenol and maintaining the temperature for 0.5-2 hours; removing the solvent to obtain the chitosan-modified polyurethane.

[0006] In a more optimized manner, the chitosan-modified polyurethane comprises the following raw materials, by mass parts: 30-35 parts polytetrahydrofuran ether diol-2000, 15-20 parts isophorone diisocyanate, 5-8 parts chitosan composition, and 2-5 parts fluorophenol.

[0007] In a more optimized manner, the chitosan composition is a composite filler-modified chitosan and an oleic acid-modified chitosan with a mass ratio of (3~6):(2~4).

[0008] In a more optimized manner, the preparation of the oleic acid modified chitosan includes the following steps: dissolving chitosan in an aqueous solution of glacial acetic acid, adding methanol and stirring until clear, adding sodium iodide, oleic acid anhydride and pyridine, stirring and mixing, reacting at 75~80℃ for 8~12h, washing, filtering and drying to obtain oleic acid modified chitosan.

[0009] In a more optimized manner, the preparation of the composite filler modified chitosan includes the following steps: water, hydrochloric acid, and titanium trichloride are mixed evenly, activated carbon is added, and the mixture is hydrothermally treated at 150~160℃ for 20~30h, washed, filtered, and dried to obtain a titanium dioxide-loaded modified activated carbon composite filler; chitosan is dissolved in glacial acetic acid aqueous solution, the titanium dioxide-loaded modified activated carbon composite filler is added, stirred evenly, glutaraldehyde is added, and the mixture is stirred at 50~60℃ for 2~3h, washed, filtered, and dried to obtain the composite filler modified chitosan.

[0010] In a more optimized manner, the oleic acid modified chitosan comprises the following raw materials, by mass parts: 1-2 parts chitosan, 30-50 parts 1% (v / v) aqueous solution of glacial acetic acid, 70-100 parts methanol, 2-4 parts sodium iodide, 4-6 parts oleic acid anhydride, and 3-4 parts pyridine.

[0011] In a more optimized manner, the titanium dioxide-loaded modified activated carbon composite filler comprises the following raw materials, by mass parts: 30-40 parts water, 6-10 parts hydrochloric acid, 8-15 parts titanium trichloride, and 20-30 parts activated carbon; the composite filler modified chitosan comprises the following raw materials, by mass parts: 1-2 parts chitosan, 30-50 parts 1% (v / v) glacial acetic acid aqueous solution, 0.3-0.5 parts titanium dioxide-loaded modified activated carbon composite filler, and 5-10 parts glutaraldehyde.

[0012] In a more optimized manner, the preparation of the filler includes the following steps: taking carbon black and silica in a mass ratio of (1~1.5):1, adding them to a modified liquid with a mass ratio of 5~10 times their total mass, stirring and reacting at 60~70℃ for 4~6h, taking out and drying to obtain the filler; the modified liquid is a vinylsilane coupling agent, ethanol and water in a mass ratio of (1~2):(20~60):(20~60).

[0013] In a more optimized manner, component A and component B are mixed at a mass ratio of (1~1.2):1 to obtain a waterproof coating. The coating is then allowed to stand and cure at 20~25℃ for 1~2 hours, followed by baking at 80~90℃ to obtain a waterproof coating.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: it includes two components, A and B; chitosan powder is added to component A, whose molecular chain contains abundant amino and hydroxyl groups, which can chemically react with formaldehyde molecules and effectively remove formaldehyde through chemical adsorption; in order to improve the dispersibility of chitosan powder in coatings, this scheme prepares chitosan-modified polyurethane as a matrix and introduces chitosan composition; the introduction of chitosan structure into polyurethane segments can improve its mechanical properties, while improving the compatibility between the matrix and chitosan powder, and improving the overall properties;

[0015] Because chitosan is hydrophilic, its addition would increase water absorption. Therefore, in the chitosan composition of this invention, oleic acid anhydride is used to modify chitosan, improving its hydrophobicity and introducing a double bond structure, which helps to improve the degree of crosslinking in subsequent steps and reactions with component B. Simultaneously, the chitosan composition also includes a modified activated carbon composite filler loaded with titanium dioxide. Titanium dioxide is a photocatalyst with excellent formaldehyde decomposition ability, while activated carbon fixes formaldehyde through adsorption. The two work synergistically to improve formaldehyde removal efficiency and reduce secondary pollution. The chitosan modified with the above composite filler and the oleic acid modified chitosan are mixed in a certain mass ratio to obtain a chitosan composition, which is introduced into the polyurethane structure as a chain extender. This can produce chitosan-modified polyurethane with good mechanical properties, good water resistance, strong formaldehyde removal ability, and good compatibility with chitosan powder.

[0016] Component B includes hydrogen-containing silicone oil and a hydrosilylation catalyst. After mixing, it can react with the double bonds in the chitosan-modified polyurethane and fillers in component A to form a network structure. This improves hydrophobicity and mechanical properties, and further enhances the overall compatibility of chitosan powder, fillers, and coatings. Detailed Implementation

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] It should be noted that there are no special restrictions on the manufacturers of the raw materials involved in this invention. Exemplary examples include: chitosan (S11064, Yuanye); wetting agent (TSF-1700, Guangzhou Hengyu Chemical); defoamer (AFE-1520, Guangzhou Rongda Chemical); hydrogen-containing silicone oil (GHQGY01, Shanhai Chemical); catalyst (Castel catalyst KS30 1000, Shenzhen Xinyongsheng New Materials); sodium iodide (CAS: 7681-82-5); oleic anhydride (CAS: 24909-68-0); pyridine (CAS: 110-86-1); concentrated hydrochloric acid (30wt% hydrochloric acid aqueous solution); titanium trichloride (CAS: 7705-07-9); activated carbon (AM-C1-064-1, Yamei Nano); polytetrahydrofuran ether diol 2000 (molecular weight 2000). Guangzhou Haoyi New Material Technology Co., Ltd.); Isophorone diisocyanate (CAS: 4098-71-9); Dibutyltin dilaurate (CAS: 77-58-7); Fluorophenol (CAS: 371-41-5); Carbon black (N330, Jiyesheng); Silica (W00063, Jiyesheng); Vinylsilane coupling agent (CAS: 1067-53-4); Ethanol (CAS: 64-17-5).

[0019] Unless otherwise specified, all figures below are parts by weight or mass ratios.

[0020] Example 1: S1: Dissolve 1 part of chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 100 parts of methanol, stir until clear, add 3 parts of sodium iodide, add 6 parts of oleic acid anhydride and 4 parts of pyridine dropwise, stir and mix well, react at 80°C for 10 h, wash, filter and dry to obtain oleic acid modified chitosan.

[0021] S2: Mix 40 parts water, 8 parts concentrated hydrochloric acid, and 12 parts titanium trichloride evenly, add 25 parts activated carbon, and perform hydrothermal treatment at 160℃ for 24 hours. Wash, filter, and dry to obtain a modified activated carbon composite filler loaded with titanium dioxide. Dissolve 1 part chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 0.4 parts of modified activated carbon composite filler loaded with titanium dioxide, stir evenly, add 8 parts glutaraldehyde, stir at 60℃ for 3 hours, wash, filter, and dry to obtain a composite filler modified chitosan.

[0022] S3: Mix the composite filler-modified chitosan and oleic acid-modified chitosan at a mass ratio of 5:3 to obtain a chitosan composition;

[0023] S4: Add 30 parts of polytetrahydrofuran ether diol 2000 and 20 parts of isophorone diisocyanate to 100 parts of ethyl acetate, stir evenly, add 0.04 parts of dibutyltin dilaurate dropwise, react at 77°C for 4 hours, add 8 parts of chitosan composition, add 0.01 parts of dibutyltin dilaurate, react at 77°C for 6 hours, add 4 parts of fluorophenol for end capping, keep warm for 1 hour, remove solvent to obtain chitosan modified polyurethane;

[0024] S5: Take carbon black and silica in a mass ratio of 1.5:1, add them to a modified liquid with a mass ratio of 10 times their total mass, stir and react at 70°C for 4 hours, take out and dry to obtain the filler; the modified liquid is a vinyl silane coupling agent, ethanol and water in a mass ratio of 1:60:20.

[0025] S6: Mix 100 parts of chitosan-modified polyurethane, 6 parts of chitosan powder, 10 parts of filler, 0.1 parts of wetting agent, and 0.1 parts of defoamer to obtain component A; mix 12 parts of hydrogen-containing silicone oil and 0.01 parts of catalyst to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain waterproof coating.

[0026] Example 2: S1: Dissolve 1 part of chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 100 parts of methanol, stir until clear, add 2 parts of sodium iodide, add 4 parts of oleic acid anhydride and 3 parts of pyridine dropwise, stir and mix well, react at 80°C for 10 h, wash, filter and dry to obtain oleic acid modified chitosan.

[0027] S2: Mix 30 parts water, 6 parts concentrated hydrochloric acid, and 8 parts titanium trichloride evenly, add 20 parts activated carbon, and perform hydrothermal treatment at 160℃ for 24 hours. Wash, filter, and dry to obtain a modified activated carbon composite filler loaded with titanium dioxide. Dissolve 1 part chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 0.3 parts of modified activated carbon composite filler loaded with titanium dioxide, stir evenly, add 5 parts glutaraldehyde, stir at 60℃ for 3 hours, wash, filter, and dry to obtain a composite filler modified chitosan.

[0028] S3: Mix the composite filler-modified chitosan and oleic acid-modified chitosan at a mass ratio of 3:2 to obtain a chitosan composition;

[0029] S4: Add 30 parts of polytetrahydrofuran ether diol 2000 and 15 parts of isophorone diisocyanate to 100 parts of ethyl acetate, stir evenly, add 0.04 parts of dibutyltin dilaurate dropwise, react at 77°C for 2 hours, add 5 parts of chitosan composition, add 0.01 parts of dibutyltin dilaurate, react at 77°C for 8 hours, add 2 parts of fluorophenol for end-capping, keep warm for 1 hour, remove solvent, and obtain chitosan modified polyurethane;

[0030] S5: Take carbon black and silica in a mass ratio of 1.5:1, add them to a modified liquid with a mass ratio of 10 times their total mass, stir and react at 70°C for 4 hours, take out and dry to obtain the filler; the modified liquid is a vinyl silane coupling agent, ethanol and water in a mass ratio of 1:60:20.

[0031] S6: Mix 90 parts of chitosan-modified polyurethane, 4 parts of chitosan powder, 10 parts of filler, 0.1 parts of wetting agent, and 0.1 parts of defoamer to obtain component A; mix 10 parts of hydrogen-containing silicone oil and 0.01 parts of catalyst to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain waterproof coating.

[0032] Example 3: S1: Dissolve 2 parts of chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 100 parts of methanol, stir until clear, add 4 parts of sodium iodide, add 6 parts of oleic acid anhydride and 4 parts of pyridine dropwise, stir and mix well, react at 80°C for 10 h, wash, filter and dry to obtain oleic acid modified chitosan.

[0033] S2: Mix 40 parts water, 10 parts concentrated hydrochloric acid, and 15 parts titanium trichloride evenly, add 30 parts activated carbon, and perform hydrothermal treatment at 160℃ for 24 hours. Wash, filter, and dry to obtain a modified activated carbon composite filler loaded with titanium dioxide. Dissolve 2 parts chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 0.5 parts of modified activated carbon composite filler loaded with titanium dioxide, stir evenly, add 10 parts glutaraldehyde, stir at 60℃ for 3 hours, wash, filter, and dry to obtain a composite filler modified chitosan.

[0034] S3: Mix the composite filler-modified chitosan and oleic acid-modified chitosan at a mass ratio of 6:2 to obtain a chitosan composition;

[0035] S4: Add 35 parts of polytetrahydrofuran ether diol 2000 and 20 parts of isophorone diisocyanate to 100 parts of ethyl acetate, stir evenly, add 0.04 parts of dibutyltin dilaurate dropwise, react at 77°C for 4 hours, add 8 parts of chitosan composition, add 0.01 parts of dibutyltin dilaurate, react at 77°C for 8 hours, add 5 parts of fluorophenol for end-capping, keep warm for 1 hour, remove solvent, and obtain chitosan modified polyurethane;

[0036] S5: Take carbon black and silica in a mass ratio of 1.5:1, add them to a modified liquid with a mass ratio of 10 times their total mass, stir and react at 70°C for 4 hours, take out and dry to obtain the filler; the modified liquid is a vinyl silane coupling agent, ethanol and water in a mass ratio of 1:60:20.

[0037] S6: Mix 110 parts of chitosan-modified polyurethane, 8 parts of chitosan powder, 12 parts of filler, 0.1 parts of wetting agent, and 0.1 parts of defoamer to obtain component A; mix 15 parts of hydrogen-containing silicone oil and 0.01 parts of catalyst to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain a waterproof coating.

[0038] Comparative Example 1 (without adding hydrogen-containing silicone oil, the remaining methods and steps are the same as in Example 1): S1: Dissolve 1 part of chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 100 parts of methanol, stir until clear, add 3 parts of sodium iodide, add 6 parts of oleic acid anhydride and 4 parts of pyridine dropwise, stir and mix well, react at 80°C for 10 h, wash, filter and dry to obtain oleic acid modified chitosan;

[0039] S2: Mix 40 parts water, 8 parts concentrated hydrochloric acid, and 12 parts titanium trichloride evenly, add 25 parts activated carbon, and perform hydrothermal treatment at 160℃ for 24 hours. Wash, filter, and dry to obtain a modified activated carbon composite filler loaded with titanium dioxide. Dissolve 1 part chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 0.4 parts of modified activated carbon composite filler loaded with titanium dioxide, stir evenly, add 8 parts glutaraldehyde, stir at 60℃ for 3 hours, wash, filter, and dry to obtain a composite filler modified chitosan.

[0040] S3: Mix the composite filler-modified chitosan and oleic acid-modified chitosan at a mass ratio of 5:3 to obtain a chitosan composition;

[0041] S4: Add 30 parts of polytetrahydrofuran ether diol 2000 and 20 parts of isophorone diisocyanate to 100 parts of ethyl acetate, stir evenly, add 0.04 parts of dibutyltin dilaurate dropwise, react at 77°C for 4 hours, add 8 parts of chitosan composition, add 0.01 parts of dibutyltin dilaurate, react at 77°C for 6 hours, add 4 parts of fluorophenol for end capping, keep warm for 1 hour, remove solvent to obtain chitosan modified polyurethane;

[0042] S5: Take carbon black and silica in a mass ratio of 1.5:1, add them to a modified liquid with a mass ratio of 10 times their total mass, stir and react at 70°C for 4 hours, take out and dry to obtain the filler; the modified liquid is a vinyl silane coupling agent, ethanol and water in a mass ratio of 1:60:20.

[0043] S6: Mix 100 parts of chitosan-modified polyurethane, 6 parts of chitosan powder, 10 parts of filler, 0.1 parts of wetting agent, and 0.1 parts of defoamer to obtain a waterproof coating.

[0044] Comparative Example 2 (increased chitosan composition addition amount, other methods and steps are the same as in Example 1): S1: Dissolve 1 part chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 100 parts methanol, stir until clear, add 3 parts sodium iodide, add 6 parts oleic acid anhydride and 4 parts pyridine dropwise, stir and mix well, react at 80°C for 10 h, wash, filter and dry to obtain oleic acid modified chitosan;

[0045] S2: Mix 40 parts water, 8 parts concentrated hydrochloric acid, and 12 parts titanium trichloride evenly, add 25 parts activated carbon, and perform hydrothermal treatment at 160℃ for 24 hours. Wash, filter, and dry to obtain a modified activated carbon composite filler loaded with titanium dioxide. Dissolve 1 part chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 0.4 parts of modified activated carbon composite filler loaded with titanium dioxide, stir evenly, add 8 parts glutaraldehyde, stir at 60℃ for 3 hours, wash, filter, and dry to obtain a composite filler modified chitosan.

[0046] S3: Mix the composite filler-modified chitosan and oleic acid-modified chitosan at a mass ratio of 5:3 to obtain a chitosan composition;

[0047] S4: Add 30 parts of polytetrahydrofuran ether diol 2000 and 20 parts of isophorone diisocyanate to 100 parts of ethyl acetate, stir evenly, add 0.04 parts of dibutyltin dilaurate dropwise, react at 77°C for 4 hours, add 10 parts of chitosan composition, add 0.01 parts of dibutyltin dilaurate, react at 77°C for 6 hours, add 4 parts of fluorophenol for end-capping, keep warm for 1 hour, remove solvent, and obtain chitosan modified polyurethane;

[0048] S5: Take carbon black and silica in a mass ratio of 1.5:1, add them to a modified liquid with a mass ratio of 10 times their total mass, stir and react at 70°C for 4 hours, take out and dry to obtain the filler; the modified liquid is a vinyl silane coupling agent, ethanol and water in a mass ratio of 1:60:20.

[0049] S6: Mix 100 parts of chitosan-modified polyurethane, 6 parts of chitosan powder, 10 parts of filler, 0.1 parts of wetting agent, and 0.1 parts of defoamer to obtain component A; mix 12 parts of hydrogen-containing silicone oil and 0.01 parts of catalyst to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain waterproof coating.

[0050] Comparative Example 3 (reduced chitosan composition addition amount, other methods and steps are the same as in Example 1): S1: Dissolve 1 part chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 100 parts methanol, stir until clear, add 3 parts sodium iodide, add 6 parts oleic acid anhydride and 4 parts pyridine dropwise, stir and mix well, react at 80°C for 10 h, wash, filter and dry to obtain oleic acid modified chitosan.

[0051] S2: Mix 40 parts water, 8 parts concentrated hydrochloric acid, and 12 parts titanium trichloride evenly, add 25 parts activated carbon, and perform hydrothermal treatment at 160℃ for 24 hours. Wash, filter, and dry to obtain a modified activated carbon composite filler loaded with titanium dioxide. Dissolve 1 part chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 0.4 parts of modified activated carbon composite filler loaded with titanium dioxide, stir evenly, add 8 parts glutaraldehyde, stir at 60℃ for 3 hours, wash, filter, and dry to obtain a composite filler modified chitosan.

[0052] S3: Mix the composite filler-modified chitosan and oleic acid-modified chitosan at a mass ratio of 5:3 to obtain a chitosan composition;

[0053] S4: Add 30 parts of polytetrahydrofuran ether diol 2000 and 20 parts of isophorone diisocyanate to 100 parts of ethyl acetate, stir evenly, add 0.04 parts of dibutyltin dilaurate dropwise, react at 77°C for 4 hours, add 4 parts of chitosan composition, add 0.01 parts of dibutyltin dilaurate, react at 77°C for 6 hours, add 4 parts of fluorophenol for end-capping, keep warm for 1 hour, remove solvent, and obtain chitosan modified polyurethane;

[0054] S5: Take carbon black and silica in a mass ratio of 1.5:1, add them to a modified liquid with a mass ratio of 10 times their total mass, stir and react at 70°C for 4 hours, take out and dry to obtain the filler; the modified liquid is a vinyl silane coupling agent, ethanol and water in a mass ratio of 1:60:20.

[0055] S6: Mix 100 parts of chitosan-modified polyurethane, 6 parts of chitosan powder, 10 parts of filler, 0.1 parts of wetting agent, and 0.1 parts of defoamer to obtain component A; mix 12 parts of hydrogen-containing silicone oil and 0.01 parts of catalyst to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain waterproof coating.

[0056] Comparative Example 4 (using composite modified chitosan instead of chitosan composition, the remaining methods and steps are the same as in Example 1): S1: Dissolve 1 part of chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 100 parts of methanol, stir until clear, add 3 parts of sodium iodide, add 6 parts of oleic acid anhydride and 4 parts of pyridine dropwise, stir and mix well, react at 80°C for 10 h, wash, filter and dry to obtain oleic acid modified chitosan;

[0057] S2: Mix 40 parts water, 8 parts concentrated hydrochloric acid, and 12 parts titanium trichloride evenly, add 25 parts activated carbon, and perform hydrothermal treatment at 160℃ for 24 hours. Wash, filter, and dry to obtain modified activated carbon composite filler loaded with titanium dioxide.

[0058] S3: Dissolve 1 part of oleic acid modified chitosan in 40 parts of 1% (v / v) glacial acetic acid aqueous solution, add 0.4 parts of modified activated carbon composite filler loaded with titanium dioxide, stir evenly, add 8 parts of glutaraldehyde, stir at 60℃ for 3h, wash, filter and dry to obtain composite modified chitosan.

[0059] S4: Add 30 parts of polytetrahydrofuran ether diol 2000 and 20 parts of isophorone diisocyanate to 100 parts of ethyl acetate, stir evenly, add 0.04 parts of dibutyltin dilaurate dropwise, react at 77°C for 4 hours, add 8 parts of chitosan composition, add 0.01 parts of dibutyltin dilaurate, react at 77°C for 6 hours, add 4 parts of fluorophenol for end capping, keep warm for 1 hour, remove solvent to obtain chitosan modified polyurethane;

[0060] S5: Take carbon black and silica in a mass ratio of 1.5:1, add them to a modified liquid with a mass ratio of 10 times their total mass, stir and react at 70°C for 4 hours, take out and dry to obtain the filler; the modified liquid is a vinyl silane coupling agent, ethanol and water in a mass ratio of 1:60:20.

[0061] S6: Mix 100 parts of chitosan-modified polyurethane, 6 parts of chitosan powder, 10 parts of filler, 0.1 parts of wetting agent, and 0.1 parts of defoamer to obtain component A; mix 12 parts of hydrogen-containing silicone oil and 0.01 parts of catalyst to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain waterproof coating.

[0062] Performance test: Take the waterproof coatings prepared in Examples 1-3 and Comparative Examples 1-4, let them stand at 25℃ for 1 hour to cure, and bake them at 80℃ to cure, and obtain the waterproof coatings; (1) Refer to GB / T19250-2013 to test the tensile strength; (2) Test the water absorption rate; (3) Apply the waterproof coating to the four walls of a 10×10×2.5m enclosed room, with a coating amount of 6μm, cure, place 10mL of 30% formaldehyde aqueous solution, heat it to make it completely evaporate, and measure the indoor formaldehyde concentration after 24h; see Table 1 for details;

[0063] Table 1:

[0064]

[0065] Conclusion: In Comparative Example 1, the performance was significantly reduced without the addition of hydrogen-containing silicone oil. In Comparative Examples 2 and 3, the performance was not as good as the example even after changing the amount of chitosan composition added, which shows the importance of controlling the amount added. In Comparative Example 4, the performance of the modified activated carbon composite filler with titanium dioxide directly loaded with oleic acid-modified chitosan instead of the chitosan composition was reduced due to steric hindrance and grafting rate. In summary, the waterproof coating prepared by this method has excellent mechanical properties, waterproof properties, and formaldehyde adsorption properties.

[0066] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A two-component carbon-based waterproof coating, characterized in that: It includes component A and component B; component A includes the following raw materials, by mass parts: 80-120 parts chitosan-modified polyurethane, 4-8 parts chitosan, 10-12 parts filler, 0-0.1 parts wetting agent, and 0-0.1 parts defoamer; component B includes the following raw materials, by mass parts: 10-15 parts hydrogen-containing silicone oil and 0.01-0.02 parts hydrosilylation catalyst; The preparation of the chitosan-modified polyurethane includes the following steps: adding polytetrahydrofuran ether diol and isophorone diisocyanate to ethyl acetate and stirring evenly, adding dibutyltin dilaurate dropwise, reacting at 75~77℃ for 2~4h, adding chitosan composition, adding more dibutyltin dilaurate, continuing to react at 75~77℃ for 4~8h, adding fluorophenol, keeping the reaction at the temperature for 0.5~2h, removing the solvent, and obtaining chitosan-modified polyurethane; The chitosan-modified polyurethane comprises the following raw materials, by mass parts: 30-35 parts polytetrahydrofuran ether diol, 15-20 parts isophorone diisocyanate, 5-8 parts chitosan composition, and 2-5 parts fluorophenol. The chitosan composition is a composite filler-modified chitosan and an oleic acid-modified chitosan with a mass ratio of (3~6):(2~4). The preparation of the composite filler modified chitosan includes the following steps: water, hydrochloric acid, and titanium trichloride are mixed evenly, activated carbon is added, and the mixture is hydrothermally treated at 150~160℃ for 20~30h. After washing, filtration, and drying, a titanium dioxide-loaded modified activated carbon composite filler is obtained. Chitosan is dissolved in glacial acetic acid aqueous solution, the titanium dioxide-loaded modified activated carbon composite filler is added, and the mixture is stirred evenly. Glutaraldehyde is added, and the mixture is stirred at 50~60℃ for 2~3h. After washing, filtration, and drying, a composite filler modified chitosan is obtained.

2. The two-component carbon-based waterproof coating according to claim 1, characterized in that: The preparation of the oleic acid modified chitosan includes the following steps: dissolving chitosan in an aqueous solution of glacial acetic acid, adding methanol and stirring until clear, adding sodium iodide, oleic acid anhydride and pyridine, stirring and mixing, reacting at 75~80℃ for 8~12h, washing, filtering and drying to obtain oleic acid modified chitosan.

3. The two-component carbon-based waterproof coating according to claim 2, characterized in that: The oleic acid modified chitosan comprises the following raw materials, by mass parts: 1-2 parts chitosan, 30-50 parts 1 vol% aqueous solution of glacial acetic acid, 70-100 parts methanol, 2-4 parts sodium iodide, 4-6 parts oleic acid anhydride, and 3-4 parts pyridine.

4. The two-component carbon-based waterproof coating according to claim 1, characterized in that: The titanium dioxide-loaded modified activated carbon composite filler comprises the following raw materials, by mass parts: 30-40 parts water, 6-10 parts hydrochloric acid, 8-15 parts titanium trichloride, and 20-30 parts activated carbon; the composite filler modified chitosan comprises the following raw materials, by mass parts: 1-2 parts chitosan, 30-50 parts 1 vol% glacial acetic acid aqueous solution, 0.3-0.5 parts titanium dioxide-loaded modified activated carbon composite filler, and 5-10 parts glutaraldehyde.

5. The two-component carbon-based waterproof coating according to claim 1, characterized in that: The preparation of the filler includes the following steps: Take carbon black and silica in a mass ratio of (1~1.5):1, add them to a modified liquid with a mass ratio of 5~10 times their total mass, stir and react at 60~70℃ for 4~6h, take out and dry to obtain the filler; the modified liquid is a vinyl silane coupling agent, ethanol and water in a mass ratio of (1~2):(20~60):(20~60).

6. A method for preparing a two-component carbon-based waterproof coating according to any one of claims 1 to 5, characterized in that: Mix component A and component B at a mass ratio of (1~1.2):1 to obtain a waterproof coating. Allow it to stand at 20~25℃ for 1~2 hours to cure, and then bake it at 80~90℃ to cure, thus obtaining a waterproof coating layer.

Citation Information

Patent Citations

  • Antibacterial water-based paint

    CN107267057A

  • Antibacterial and anti-mildew interior wall latex paint

    CN110358373A